2015
DOI: 10.1016/j.fertnstert.2015.07.1133
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment algorithm for evaluation of early pregnancy after in vitro fertilization

Abstract: Our clinical algorithm for early pregnancy evaluation after ART is effective for identification and prompt intervention of EP and HP without significant over- or misdiagnosis, and avoids the potential catastrophic morbidity associated with delayed diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…[ 3 , 5 ] A recent study found that abdominal pain before HP was diagnosed was an independent risk factor for miscarriage in those with an HP. [ 7 ] However, we found that the symptoms of abdominal pain and hemoperitoneum due to rupture of the EP site did not affect the prognosis of patients with an IUP. Additionally, our study showed that the GA at treatment was earlier in the miscarriage group than it was in the nonmiscarriage group.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[ 3 , 5 ] A recent study found that abdominal pain before HP was diagnosed was an independent risk factor for miscarriage in those with an HP. [ 7 ] However, we found that the symptoms of abdominal pain and hemoperitoneum due to rupture of the EP site did not affect the prognosis of patients with an IUP. Additionally, our study showed that the GA at treatment was earlier in the miscarriage group than it was in the nonmiscarriage group.…”
Section: Discussionmentioning
confidence: 83%
“…Several previous studies proved that laparoscopic surgery is now as safe as open surgery during pregnancy, with no deleterious effects on either the mother or child. [ 7 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…This marker is substantially helpful in devoting resources to pregnancies at risk of developing an EP 4,6,10 . In their cohort of ART‐conceived pregnancies, Cookingham et al 10 . observed a β‐hCG concentration < 50 IU/L in 7.1% of studied pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…has an area under the receiver‐operating‐characteristics (ROC) curve (AUC) of 0.900 for predicting an EP and has been validated in a clinical setting in three UK hospitals 9 . Within the field of ART, Cookingham et al 10 . developed an algorithm for the evaluation of early pregnancy after IVF, which identified 96.7% and 83.3% of EPs and heterotopic pregnancies, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The initial β-human chorionic gonadotropin (hCG) level and hCG rise are less predictive of HP. [ 4 ] And EP lesion might be too small to be detected on transvaginal sonography (TVS) at early stage or be ignored by clinicians who found a visible intrauterine sac. It is worthy to be familiar with clinical characteristics and risk factors of HP after in vitro fertilization (IVF).…”
Section: Introductionmentioning
confidence: 99%